Public administration in the implementation of preventive anti-corruption mechanisms: A case study of anti-corruption declaration in times of martial law - Негара, Родіон Віталійович; Негара, Р. В.; Nehara, Rodion V.; Швець, Катерина Андріївна; Швець, К. А.; Shvets, Kateryna A.; Сідор, Михайло Іванович; Сідор, М. І.; Sidor, Mykhailo I.; Берлач, Анатолій Іванович; Берлач, А. І.; Berlach, Anatolii I.; et al. (Milan : CERIDAP of the University of Milan, 2024)
The aim of this study is to identify the reasons and grounds leading to the suspension of the submission of anti-corruption electronic declarations by public servants in Ukraine, as well as to assess their appropriateness and significance at present. The authors reach the conclusion that the reinstatement of anti-corruption electronic declarations in Ukraine is currently imperative. Simultaneously, the authors propose a differentiated approach for different categories of public servants regarding declaration submissions, along with the establishment of mandatory preventive measures. Balancing these measures is crucial to the restoration process of anti-corruption electronic declarations. The subject of the study, considered a separate and independent research endeavor in Ukraine for the first time, holds prospects for further exploration, especially in the context of establishing mechanisms for implementing anti-corruption electronic declarations in times of a legal framework of martial law.
Nehara R. Public administration in the implementation of preventive anti-corruption mechanisms: A case study of anti-corruption declaration in times of martial law / Nehara R., Shvets K., Sidor M. et al. // Ceridap. – Milan : CERIDAP of the University of Milan, 2024. – 4(2024). - P. 249-269. URL: https://doi.org/10.13130/2723-9195/2024-4-140
Keywords: public administration; preventive anti-corruption mechanisms; anti-corruption electronic declarations; declarants; martial law